Dual-Band Orthogonally Polarized 20/30 GHz Reflectarray for Satellite Communication - Bharati R.; Saurabh A.K.; Meshram M.K. (My University, 2025)
A single-layer dual-band orthogonally polarized reflectarray is designed for 20/30 GHz (downlink/uplink) frequency bands. The unit cell has a meander-like circular split ring patch with cross dipole slots. The outer ring is designed for lower frequency band and the inner ring is designed for higher frequency. By varying the structure's size, a continuous 360○ phase quantization is achieved. As a result, the reflectarray demonstrates gains of 21.5 dBi at 20 GHz and 25.5 dBi at 30 GHz, with aperture efficiencies of 13 % at 20 GHz and 14.3 % at 30 GHz. Additionally, it features 1 dB gain bandwidths of 9% for 20 GHz and 5% for 30 GHz, highlighting its suitability for satellite communication applications. © 2024 IEEE.